The growing place of livestock products in world food in the twenty- first century - Delgado, Christopher L.; Rosegrant, Mark W.; Steinfeld, Henning; Ehui, Simeon; Courbois, Claude (International Food Policy Research Institute, 1999)
This paper attempts to define the nature, extent, scope, and implications of what the authors term the “Live stock Revolution” in developing countries. Looking forward to 2020, they argue that the structural shifts in world agriculture being brought about by shifts in developing-country demand for foods of animal origin will continue and that increasingly global markets have the ability to supply both cereal and animal products in desired quantities with out undue price rises. They emphasize, however, that policy decisions taken for the live stock sector of developing countries will determine whether the Live stock Revolution helps or harms the world’s poor and malnourished. (from Foreward by Per Pinstrup-Andersen)